Acute vestibular syndrome accompanying middle cerebral artery infarctions: a single-center study - Kuloğlu Pazarcı, Nevin; Gürsoy, Gizem; Çiftçi, Necip Kürşad (The European Research Journal, 2025)
Objectives: Acute vestibular syndrome (AVS) is a disease and disorder usually manifest with a single episode of sudden onset vestibular symptoms and signs, and may occur at any point along the vestibular pathway from the peripheral labyrinth to the vestibular cortex. This study presents the characteristics of the involved cortical area and clinical course in middle cerebral artery (MCA) territory infarction patients with central vestibular disorder. Methods: Files of patients diagnosed with acute ischemic stroke in the MCA territory were reviewed retrospectively between December 2020 and March 2022. All the patients were categorized into two groups (with or without AVS) and analyzed for comorbidities as well as smoking and drinking habits, and their data pertaining to the neurological examination, bedside neuro-otological examination, and laboratory and computerized tomography angiography findings were collected. Results: Seven hundred and sixty-eight patients with MCA territory infarction were included in the study. AVS incidence was calculated to be 13.3%. There was no statistically significant difference in the distribution of age and sex between patients with and without AVS. The involvement of the right side was significantly more prevalent in AVS patients. Distribution of patients with right-sided infarction: 11 with posterior superior temporal gyrus 17 with parieto-insular cortex, 16 with insular cortex and temporoparietal junction together, and 18 with more than one millimetric infarction in all three areas. Conclusions: Patients with acute vestibular syndrome, may have infarctions in the anterior circulation and most of them had no pathological neuro-otologic test findings.